2017
DOI: 10.1177/0009922817728699
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Multicenter Study of Clinical Tests of Neonatal Purulent Meningitis

Abstract: This study aimed to provide more data support for early diagnosis and treatment of neonatal purulent meningitis through retrospective analysis of its clinical diagnosis and treatment, pathogen distribution, and drug resistance in 5 third-class A hospitals in Southwest and Northwest China from January 2011 to December 2015. It was found that both the positive rates of blood and cerebrospinal fluid culture were low, and Escherichia coli should be the main pathogenic bacteria. Drug-resistant strains with varying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 28 publications
1
11
0
1
Order By: Relevance
“…The wide usage of broad-spectrum antibiotics has fueled the emergence of drug-resistant strains of E. coli, which poses a great challenge in the treatment of neonatal bacterial infections. Several recent studies have found that E. coli is widely resistant to ampicillin and shows different degrees of resistance to the thirdgeneration cephalosporins [2,7]. However, the drug resistance profile of E. coli shows considerable interregional variability depending on the local pattern of antibiotic use, which is worthy of further study.…”
Section: Introductionmentioning
confidence: 99%
“…The wide usage of broad-spectrum antibiotics has fueled the emergence of drug-resistant strains of E. coli, which poses a great challenge in the treatment of neonatal bacterial infections. Several recent studies have found that E. coli is widely resistant to ampicillin and shows different degrees of resistance to the thirdgeneration cephalosporins [2,7]. However, the drug resistance profile of E. coli shows considerable interregional variability depending on the local pattern of antibiotic use, which is worthy of further study.…”
Section: Introductionmentioning
confidence: 99%
“…Forty-nine cases of children with purulent meningitis (mean ± SD: 15.5±17.0 months, range 2-89 months; 19 female) were collected from January 2016 to December 2018 in Beijing Children's Hospital of Capital Medical University. The criteria for a definite diagnosis of bacterial meningitis included [12,13] : (1) isolation of bacterial pathogens in one or more CSF cultures; (2) classic clinical manifestations including fever, headache, stiff neck, consciousness disturbance, and sign of meningeal irritation; (3) typical CSF findings including leukocyte counts > 0.1x109/L with predominant polymorphonuclear cells. All patients had been assessed by the Glasgow Outcome Scale GOS) ( Table 1), and rated as good prognosis if the GOS score was 5, and as poor prognosis if the GOS score was 1 to 4.…”
Section: Subjectsmentioning
confidence: 99%
“… 13 A retrospective study conducted by Zhao et al showed that E. coli remains a prominent pathogen of NM. 14 Antibiotic treatment has always been a routine treatment for this infection. However, because of the emergence of drug-resistant bacteria, the curative effects of antibiotics have decreased.…”
Section: Introductionmentioning
confidence: 99%